Cardiac calcification as a marker of subclinical atherosclerosis and predictor of cardiovascular events: A review of the evidence. (July 2019) - Faggiano, Pompilio; Dasseni, Nicolò; Gaibazzi, Nicola; Rossi, Andrea; Henein, Michael; Pressman, Gregg
Risk prediction of future atherothrombotic cardiovascular events is currently based on conventional risk factor assessment and the use of validated algorithms, such as the Framingham Risk Score, the Pooled Cohort Equations, and the European SCORE Risk Charts. However, the identification of subclinical organ damage has emerged as a potentially more accurate predictor of individual risk. Several imaging modalities have been proposed for identification of preclinical atherosclerosis. Coronary artery calcification scanning performed using cardiac computed tomography and calculation of the Agatston score is the most commonly used technique in clinical practice for detection of subclinical disease, prognostic stratification of asymptomatic individuals and implementation of preventive strategies. Furthermore, conventional echocardiographic examination may offer an assessment of cardiac calcifications at different sites, such as the mitral apparatus (including annulus, leaflets and papillary muscles), aortic valve and ascending aorta, that are associated with the clinical manifestation of atherosclerotic disease and are predictive of future cardiovascular events. The aim of this paper is to summarize available evidence on the clinical use of cardiac calcification, review the pathogenetic mechanisms involved, including similarities with atherosclerosis, and evaluate its potential for risk stratification and prevention of clinical events in the primary prevention setting.